Benefits of Motivational lnterviewing application for patients and Healthcare professionals - Szczekała, Katarzyna; Wiktor, Krzysztof; Kanadys, Katarzyna; Wiktor, Henryk (Polish Journal of Public Health, 2019)
Motivational Interviewing (MI) is a collaborative, goal-oriented and focused on change, style of communication. It is characterised by the MI provider’s empathy, understanding, mental and emotional attitudes towards the patient. This non-judgemental conversation is aimed at strengthening inner motivation and commitment to attain the goal and is based solely on the individual’s reasons for change. The initial application of MI in clinical psychology has been modified appropriately to allow for its use in health care, rehabilitation, public health, social work, dentistry, social rehabilitation, coaching and education. It is recommended for introducing new behaviours, lifestyles and therapeutic adherence. The application of MI contributes to the enhancement of patient-healthcare worker communication, the patient’s concordance and compliance. On the other hand, learning and adopting this method in counselling is useful for healthcare professionals. In treatment, greater patient awareness and obedience lead to more conscientious responsibility for treatment and health, which in turn, produces better therapy outcomes that serve as confirmation of the merit of the therapy prescribed. The application of MI contributes to health professionals’ greater success, satisfaction, self-confidence and a sense of self-efficacy. The aim of this work is to present the essential features of MI as well as some interesting examples of research showing the benefits of using MI and ideas for training it. Non-systematic literature review of the years 2005-2018 on the use of MI in health promotion in PubMed provided evidence of wide use of MI by healthcare professionals